Kajian Tekno Ekonomi Dalam Pengembangan Sistem Industri Sabut Kelapa Untuk Usaha Kecil Dan Menengah Di Sulawesi Utara - Tooy, Dedie; Rumambi, David Paul; Waney, Nordy Fritsgerald Lucky; Montolalu, Maya; Manginsela, Elsje Pauline (Sam Ratulangi University, 2023)
The coconut industry in North Sulawesi has not maximized coconut husk in its business. Most only use the flesh as copra, crude oil (CCO), and cooking oil. From several research results, it turns out that the portion of coconut husk utilization is still very limited in management, and even thrown away. This study aims to analyze the technological and economic feasibility (techno-economy) of the development of the coconut husk industrial system as an effort to provide stakeholder considerations in increasing the value and income of coconut farmers in North Sulawesi. This research was conducted for three months with survey locations in 2 (two) coconut producing areas in North Sulawesi Province, namely South Minahasa Regency and Bitung City. The research method was carried out by conducting surveys and interviews with coconut farmers, entrepreneurs, local government agencies and with experts, then calculating and studying several parameters for measuring the economic value of alternative technologies and equipment used. The results showed that from the measurement of the NPV (Net Present Value), net B/C ratio, IRR (Internal Rate of Return) and PP (Payback Period) it is known that several alternative systems for the development of the coconut husk industry with fiber, cocopeat and rope products are feasible to be developed in South Minahasa Regency and Bitung City. Several things that are very important in the feasibility of developing this agro-industrial system are equipment technology (process), prices of processed products (output) and a continuous market/off taker. The investment value of processing equipment technology is relatively high, so to increase the enthusiasm of small and medium enterprises (SMEs) it really needs government intervention in equipment technology assistance and market certainty.